An Early Clinical Study of Time-Domain Microwave Radar for Breast Health Monitoring - Porter, Emily; Coates, Mark; Popovic, Milica (IEEE transactions on biomedical engineering, 2016)
This study reports on monthly scans of healthy patient volunteers with the clinical prototype of a microwave imaging system. The system uses time-domain measurements, and incorporates a multistatic radar approach to imaging. It operates in the 2-4 GHz range and contains 16 wideband sensors embedded in a hemispherical dielectric radome. The system has been previously tested on tissue phantoms in controlled experiments. With this system prototype, we scanned 13 patients (26 breasts) over an eight-month period, collecting a total of 342 breast scans. The goal of the study described in this paper was to investigate how the system measurements are impacted by multiple factors that are unavoidable in monthly monitoring of human subjects. These factors include both biological variability (e.g., tissue variations due to hormonal changes or weight gain) and measurement variability (e.g., inconsistencies in patient positioning, system noise). For each patient breast, we process the results of the monthly scans to assess the variability in both the raw measured signals and in the generated images. The significance of this study is that it quantifies how much variability should be anticipated when conducting microwave breast imaging of a healthy patient over a longer period. This is an important step toward establishing the feasibility of the microwave radar imaging system for frequent monitoring of breast health.